2015
DOI: 10.1161/circoutcomes.114.001613
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Women Veterans Undergoing Cardiac Catheterization in the Veterans Affairs Healthcare System

Abstract: C oronary artery disease (CAD) remains the leading cause of death among women in the United States.1 Prior research has demonstrated that women with CAD are typically older than men and have more risk factors, such as diabetes mellitus, 2 hypertension, 3,4 hyperlipidemia, 5 obesity, 6 and congestive heart failure.4,7 Despite these higher rates of CAD risk factors, women have less obstructive CAD. 4,8 Studies are conflicting regarding whether women are treated less aggressively than their male counterparts. 9-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Our results are also consistent with the results from a 2015 report focused on cardiac catheterization characteristics among more than 3000 female armed forces Veterans (as opposed to the civilian WISE sample; Davis et al, 2015). Similar to the WISE results reported here, female Veterans obtaining cardiac catheterization in the latter study showed low rates of obstructive CAD but relatively high rates of psychiatric comorbidities such as depression and anxiety (e.g., 55.3 and 20.1 % of the women in the latter sample met criteria for depression and posttraumatic stress disorder based on medical chart review).…”
Section: Discussionsupporting
confidence: 89%
“…Our results are also consistent with the results from a 2015 report focused on cardiac catheterization characteristics among more than 3000 female armed forces Veterans (as opposed to the civilian WISE sample; Davis et al, 2015). Similar to the WISE results reported here, female Veterans obtaining cardiac catheterization in the latter study showed low rates of obstructive CAD but relatively high rates of psychiatric comorbidities such as depression and anxiety (e.g., 55.3 and 20.1 % of the women in the latter sample met criteria for depression and posttraumatic stress disorder based on medical chart review).…”
Section: Discussionsupporting
confidence: 89%
“…Adjusted outcomes at 1 year showed females had lower mortality (HR, 0.74; 95% CI, 0.60–0.92) and less all-cause rehospitalization (HR, 0.87; 95% CI, 0.82–0.93), but there was no difference in rates of unplanned PCI. 37 …”
Section: Quality Of Carementioning
confidence: 99%
“…Overall estimates in women and men from the Veterans Administration Cardiovascular Assessment Reporting and Tracking System,16 the National Cardiac Data Registry, and the National Heart, Lung, and Blood Institute–sponsored Women's Ischemia Syndrome Evaluation (WISE)10 databases indicate that there are at least 3 to 4 million American women and men with stable INOCA. Incurred healthcare costs are similar to those for obstructive CAD.…”
Section: Inoca—prevalencementioning
confidence: 99%